Perlindungan Hukum Pelaku Gadai Syariah Menurut Hukum Positif Indonesia - Tina Amelia (Fakultas Syariah IAIN Kediri, 2024)
The study focuses on the application of the concept of Gadai Syariah (Rahn) as a legal framework for the management of the financial sector. Gadai Syariah is a legal framework that aims to regulate the financial sector and its relationship with the economy. It is based on the principles of economics, which emphasize the importance of the financial sector in managing the financial sector. The research aims to understand the role of the financial sector in the development of Indonesia, particularly in the context of the country's economic development and the need for credit. The study also examines the role of the financial sector in the internationalization of Indonesia and the modernization of the country.Gadai is a legal framework that aims to regulate the financial sector, focusing on the role of the financial sector in the development of Indonesia. The study also discusses the role of the financial sector in the development of Indonesia, highlighting the importance of the financial sector in the development of Indonesia. The study also discusses the role of the financial sector in the development of Indonesia, highlighting the role of the financial sector in the development of Indonesia. Penelitian ini berfokus pada penerapan konsep Gadai Syariah (Rahn) sebagai kerangka hukum pengelolaan sektor keuangan. Gadai Syariah merupakan kerangka hukum yang bertujuan untuk mengatur sektor keuangan dan hubungannya dengan perekonomian. Hal ini didasarkan pada prinsip-prinsip ekonomi, yang menekankan pentingnya sektor keuangan dalam mengelola sektor keuangan. Penelitian ini bertujuan untuk memahami peran sektor keuangan dalam pembangunan Indonesia, khususnya dalam konteks pembangunan ekonomi negara dan kebutuhan akan kredit. Penelitian ini menggunakan penelitian yuridis normatif, dan akan diarahkan untuk mengkaji peran sektor keuangan dalam internasionalisasi Indonesia dan modernisasi negara. Gadai merupakan kerangka hukum yang bertujuan untuk mengatur sektor keuangan, dengan fokus pada peran sektor keuangan dalam pembangunan Indonesia. Penelitian ini juga membahas peran sektor keuangan dalam pembangunan Indonesia, menyoroti pentingnya sektor keuangan dalam pembangunan Indonesia. Penelitian ini juga membahas peran sektor keuangan dalam pembangunan Indonesia, menyoroti peran sektor keuangan dalam pembangunan Indonesia.